Role of the skin microbiota and intestinal microbiome in rosacea - Zhu, Weitao; Hamblin, Michael R.; Wen, Xiang (Frontiers in Microbiology, 2023)
Rosacea is a chronic inflammatory cutaneous disorder of vague causes that mainly affects the centrofacial region, including cheeks, nose, chin, forehead and eyes. The pathogenesis of rosacea remains unclear because it involves several complex factors. Additionally, the potential treatment methods need to be explored. We reviewed the common bacterial species in the skin microbiota and gut microbiota of rosacea patients such as Demodex folliculorum, Staphylococcus epidermidis, Bacillus oleronius, Cutibacterium acnes, Helicobacter pylori, and identified their role in the pathogenesis. Besides, we summarized the influence factors such as temperature and age on rosacea patients. We also systematically reviewed the commonly used clinical treatment methods, including antibiotics, probiotics. as well as their treatment mechanism and application precautions